Cultivating Movement for Students with Special Needs Through Creative Gymnastics to Maintain Physical Fitness - Wijayanti, Dwi Gansar Santi; Yuwono, Cahyo; Rizqanada, Ayutisa; Berlianti, Dinar; Tadita, Armayta Dwi; Pamungkas, Dimas Bagus Aji; Ngatinah, Ngatinah (Jurnal Abdimas, 2024)
Children with Special Needs (ABK) are children with their own characteristics, so that is what distinguishes them from other children. Special attention to the education and health aspects for students with special needs is very important. Various efforts have been made by the local government to provide great attention to this by establishing educational unit facilities, namely the State Special School in Semarang Regency. Physical Education can be used as one way to cultivate movement for students with special needs. The methods of implementing this service include coordination and socialization, implementation of creative gymnastics and assistance. Creative gymnastics activities are carried out and adjusted to the abilities of students with special needs. Starting from warm-up, core, and cool-down movements. Creative gymnastics combines movements that are easy to do so that students can imitate and move actively. Gymnastics movements are able to stimulate all aspects of cognitive, affective, psychomotor or sensory abilities responsively. Cultivating movement in students with special needs will help them maintain their physical fitness. So that they are not only healthy but they are also able to carry out other activities without feeling tired